Displacing Gender: A Study of Mahesh Dattani‟s Dance Like a Man - A, Veena; S, Dhanya K (International Journal of Psychosocial Rehabilitation, 2020)
Gender” and “sex” always have been two terms in constant dispute. “Femininity” and “masculinity” and two different gender identities shaped by socio cultural processes. For ages literature and arts have been constructing various stereotypical ideologies upon masculine and feminine concepts. Mahesh Dattani is one among the prominent visual artists who possessed „gender‟ as the principal concern in his plays like Tara, Dance Like a Man, Final Solutions etc. He provided an effective dramatic voice for the marginalized victims through his fragmented settings and other postmodern theatrical attempts. In his play Dance Like a Man Dattani questions the hitherto erected socio-cultural constructions of gender. Dattani devises the traditional dance as a medium to portray the gender conflicts and allied issue in his society through three generations.